'URBAN & SUBURBAN NATURE INTERACTIONS', IMPACTS AND SERENDIPITOUS NARRATIVES OF THE MY NATUREWATCH PROJECT. (May 2020) - Phillips, R.; Anderson, R.; Abbas-Nazari, A.; Gaver, B.; Boucher, A.
Abstract: The My Naturewatch project uses self-build wildlife cameras supporting new public engagements with nature & technology. The project used Open Design methods providing self-defined, bespoke making outputs, modelling 'environmental citizenship', transitioning beyond sustainability. By co-designing makers were encouraged to engage with ecosystems refocusing human habitats & perspectives driven by curiosity. The article shares a qualitative evaluation of the project's impact on participants, describing attitudes, understanding and behaviour towards technology & nature changed by participation.